Germplasm collection, multiplication, evaluation and distribution - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1985)
The collection of Phaseolus of the CIAT Genetic Resources Unit reached a total of 34,312 accessions in 1984. Of these, 89.0 percent corresponds to P. vulgaris, 7.0 percent to P. lunatus, 3.5 percent to P. coccineus, 0.6 percent to P. acutifolius, and 0.2 percent to wild noncultivated species. An intensive search was conducted for information on the site of origin of the P. vulgaris germplasm of those materials already increased and held at CIAT. Both the donor country and the origin were compared with 2 important characters in common beans: seed size and growth habit. Concerning other Phaseolus species, more than 200 accessions of P. coccineus have been processed; a complete characterization of most of the P. acutifolius collection (166 accessions) is underway at 2 locations (at 800 and 1000 m.a.s.l.). It includes both the cultivated forms and the wild ancestral types. (CIAT)